A Language Skills Content Analysis From English Textbooks For Junior High School Grade 7 - Cynantia Rachmijati; Sri Supiah Cahyati (JELLE : Journal Of English Literature, Linguistics, and Education, 2020)
Textbook is one of the main sources for teachers and learners, it serves as a teaching aid and important teaching and learning material. This research entitled “A Language Skills Content Analysis from English Textbooks for Junior High School Grade 7” aimed to analyze the language skills presented in the English textbooks. The research employed qualitative content analyzes method as the research method. A checklist was used to collect the data, then presented in the percentages. The result showed that the book “When English Rings the Bell” focused more on Speaking skills (35%), whereas “English in Focus” focused more on Writing skills (48%). Meanwhile, based on the standard of BNSP, students in Junior High school should be able to reach the functional level of literacy by practicing listening, speaking, reading, and writing in English. Both books have appropriate proportion to support students’ literacy skills.Keywords: Textbook, Content Analysis, Language Skills